2015
DOI: 10.1128/jcm.00295-15
|View full text |Cite
|
Sign up to set email alerts
|

Dual Invasive Infection with Phaeoacremonium parasiticum and Paraconiothyrium cyclothyrioides in a Renal Transplant Recipient: Case Report and Comprehensive Review of the Literature of Phaeoacremonium Phaeohyphomycosis

Abstract: e Despite increasing reports of human infection, data about the optimal care of Phaeoacremonium infections are missing. We report a case of an infection due to Phaeoacremonium parasiticum and Paraconiothyrium cyclothyrioides, initially localized to skin and soft tissue, in a kidney transplant patient. Despite surgical drainage and excision of the lesion and combination antifungal therapy with voriconazole and liposomal amphotericin B, a disseminated infection involving the lungs and brain developed and led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 63 publications
3
57
0
Order By: Relevance
“…Also, unsuccessful treatment of P. rubrigenum subcutaneous infections with itraconazole (MICs of Ͼ8 g/ml) has been on record (8). Similar to our findings, low MICs of voriconazole and posaconazole among the azoles were noted in a recent review of antifungal susceptibility data from eight Phaeoacremonium isolates by Colombier et al (3). A recent European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and European Confederation of Medical Mycology (ECMM) joint clinical guideline for the diagnosis and management of systemic phaeohyphomycosis recommends triazoles for the treatment of infections by melanized fungi (32).…”
supporting
confidence: 79%
See 3 more Smart Citations
“…Also, unsuccessful treatment of P. rubrigenum subcutaneous infections with itraconazole (MICs of Ͼ8 g/ml) has been on record (8). Similar to our findings, low MICs of voriconazole and posaconazole among the azoles were noted in a recent review of antifungal susceptibility data from eight Phaeoacremonium isolates by Colombier et al (3). A recent European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and European Confederation of Medical Mycology (ECMM) joint clinical guideline for the diagnosis and management of systemic phaeohyphomycosis recommends triazoles for the treatment of infections by melanized fungi (32).…”
supporting
confidence: 79%
“…In a recent comprehensive review by Gramaje et al (2) on the nomenclature of this genus, 11 Phaeoacremonium species have been confirmed as human opportunistic pathogens causing infections in both immunocompromised and immunocompetent hosts. The most frequent species identified in human infections are P. parasiticum, P. inflatipes, and P. rubrigenum (3,4). Furthermore, since 2006 many new cases of Phaeoacremonium infections implicating other species such as P. krajdenii, P. venezuelense, P. minimum, and P. aleophilum have been described (4)(5)(6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although Paraconiothyrium cyclothyrioides was relatively common in our studied samples, there are only two clinical reports that refer to this species. Both cases are from immunocompromised patients; in one case P. cyclothyrioides caused skin lesions of the lower extremities, and in the second case it produced a systemic coinfection together with Phaeoacremonium parasiticum (37,38). Even though Phoma sporulates easily, it is commonly misidentified as other related genera, such as Ascochyta, because the genera have similar morphologies, physiologies, and nucleotide sequences (39,40).…”
Section: Discussionmentioning
confidence: 99%